Komposisi, Dominansi, dan Pemanfaatan Gulma Agroforestri Jambu Mete (Anacardium occidentale L.) di Desa Gemawang Kecamatan Ngadirojo Kabupaten Wonogiri - Asri Khoirunisa; Santhyami Santhyami (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Gemawang Village, Ngadirojo District, Wonogiri Regency, Central Java Province is home to one of the cashew (Anacardium occidentale L.)-based agroforestry operations. In agroforestry management, plants are one of the factors that can impede cashew production growth. To determine the success of weed control, it is necessary to first acquire an understanding of weed species. There were 2 stations in this study, namely cashew-based agroforestry ecosystem stations and teak monoculture ecosystems.This study assessed the composition, dominance, and prospective use of weed vegetation in cashew-based agroforestry areas. The point-intercept method and exploration of weed vegetation varieties in agroforestry station constitute the research methodology. As a comparison station, this study was also conducted on teak monocultures that are commonly found at research sites.The quadratic form measuring 1 m x 1 m with 100 grids of 12 plots at each station was utilised to collect weed samples. Composition and dominance of species in agroforestry and monoculture were found to be distinct. 24 species from 12 families are used in agroforestry, while 12 species from 7 families are used in monoculture. The dominant invasive species in agroforestry is Ageratum conyzoides L. (34.39%), while in monoculture it is Synedrella nodiflora Gaertn (37.78%). The weed vegetation diversity index value in agroforestry and monoculture was 1.90 and 1.51,respectively, which is considered moderate. In contrast, the value of the Sorensen uniformity index, which was 36.84%, was considered to be low. Up to 26 species of vegetation have the potential to contribute to human survival.